Surface Characterization of a Novel D-π-D Type Ligand by IGC at Infinite Dilution - Karaoglan, Gulnur Keser; Sakar, Dolunay (SPRINGER HEIDELBERG, 2011)
The adsorption properties and acid-base contributions to the surface energy of (E)-N-((E)-3-(4-(dimethylamino)phenyl)allylidene)-4-(4-((E)-((E))-3-(4(dimethylamino)phenyl)allylidene)amino)-3-methylnaphthalen-1-yl)-2-ethylnaphthalen-1-amine which is a new D-pi-D Type Schiff base ligand (L) were determined by inverse gas chromatography (IGC) at infinite dilution. The retentions of several organic solvents on L were measured in the temperature range from 40 to 100 A degrees C by IGC. The dispersive component of the surface energy, and the acid, K (A) and base, K (D) constants for the L were calculated. The obtained results proved that IGC is an efficient and successful technique for the characterization of adsorption properties and acid-base quantity of these kinds of materials.
Keywords: Inverse gas chromatography; Surface and adsorption thermodynamic parameters; Lewis acid-base constants; New D-pi-D type Schiff base ligand; INVERSE GAS-CHROMATOGRAPHY; ANTIBACTERIAL ACTIVITY; CARBON-BLACK; ADSORPTION; COMPLEXES; MOLECULES; ENERGY; CELLULOSE; POLYMERS; ALUMINA; Biochemistry & Molecular Biology; Chemistry